2009
DOI: 10.1016/j.biopsych.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Overexpression of ΔJunD Resets L-DOPA-Induced Dyskinesia in a Primate Model of Parkinson Disease

Abstract: Background Involuntary movements, or dyskinesia, represent a debilitating complication of dopamine replacement therapy for Parkinson disease (PD). The transcription factor ΔFosB accumulates in the denervated striatum and dimerizes primarily with JunD upon repeated L-DOPA administration. Previous studies in rodents have shown that striatal ΔFosB levels accurately predict dyskinesia severity, and indicate that this transcription factor may play a causal role in dyskinesia sensitization process. Methods We aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 38 publications
(72 reference statements)
3
63
0
Order By: Relevance
“…Furthermore, and this is perhaps the most convincing evidence in favor of a direct etiological role of DFosB in LID, striatal overexpression of DFosB induced by viral vector led to the development of a dyskinetic phenotype similar to LI-AIMs, in the absence of L-DOPA administration, in the 6-OHDA-lesioned rat (Cao et al, 2010). In addition, in a study performed in the MPTP-lesioned macaque, a linear relationship was demonstrated between striatal DFosB levels and dyskinesia severity (Berton et al, 2009). The results of the studies cited above suggest that DFosB is involved in the pathophysiology of LID but also introduce the idea of a critical threshold above which it generates dyskinesia.…”
Section: A Transcription Factorsmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, and this is perhaps the most convincing evidence in favor of a direct etiological role of DFosB in LID, striatal overexpression of DFosB induced by viral vector led to the development of a dyskinetic phenotype similar to LI-AIMs, in the absence of L-DOPA administration, in the 6-OHDA-lesioned rat (Cao et al, 2010). In addition, in a study performed in the MPTP-lesioned macaque, a linear relationship was demonstrated between striatal DFosB levels and dyskinesia severity (Berton et al, 2009). The results of the studies cited above suggest that DFosB is involved in the pathophysiology of LID but also introduce the idea of a critical threshold above which it generates dyskinesia.…”
Section: A Transcription Factorsmentioning
confidence: 84%
“…Taken together, these data do not support an involvement of JunD or JunB in LID. However, in the MPTP-lesioned macaque, striatal overexpression of DJunD induced by adeno-associated viral vector alleviated LID in primed animals upon subsequent L-DOPA administration without impairing its antiparkinsonian action (Berton et al, 2009). Although that study did not establish a causative role played by DJunD in LID, it certainly established an antidyskinetic effect of intrastriatal delivery of DJunD.…”
Section: A Transcription Factorsmentioning
confidence: 84%
“…Four species have been regularly used, namely the macaque monkeys (macaca mulatta and macaca fascicularis) Berton et al 2009;Ahmed et al 2010;Fasano et al 2010;Rylander et al 2010), the marmoset (callithrix jacchus) (Pearce et al 1998;Henry et al 2001Henry et al , 2003Smith et al 2002;Savola et al 2003;Hill et al 2004a,b) and the squirrel (Saimiri sciureus) monkeys Hsu et al 2004), although the most human-like ones are displayed by the macaques (Bezard et al 2001a;Jenner 2008). Those macaques with LID show various combinations of choreic-athetoid (i.e., characterized by constant writhing and jerking motions), dystonic and even ballistic movements (i.e., large-amplitude flinging, flailing movements), although less frequently for those latter Gold et al 2007;Berton et al 2009;Ahmed et al 2010;Fasano et al 2010;Rylander et al 2010). Both the repertoire and severity of dyskinesia are not distinguishable from LID occurring in PD patients (e.g., Bezard et al 2003;Ahmed et al 2010;Fasano et al 2010).…”
Section: Dyskinesiamentioning
confidence: 99%
“…Increased striatal expression of a splicing isoform of Fosb (DFosb) was associated with progression of Parkinson's disease (Tekumalla et al 2001). Moreover, striatal overexpression of DFosb in rats (Cao et al 2010) or of a dominant negative DFosb inhibitor in primates (Berton et al 2009) increased or decreased, respectively, the development of involuntary movement disorders in animal models of Parkinson's disease. Given these similarities to Parkinson's disease, our results support the possibility that cystamine administration could prevent or delay the onset of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%